2018
DOI: 10.3390/c4010009
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Incorporation of Phosphorus Functionalities on Carbon Nanofibers: Effects on the Catalytic Performance of Fructose Dehydration

Abstract: Phosphorylated carbons have been reported to be effective catalysts in dehydration reactions for biomass valorization. The amount and the nature of P groups are a key parameter affecting the catalytic performances of functionalized materials. Herein, we investigate the role of structural and surface properties of carbon-based materials, specifically carbon nanofibers, in determining the amount of P-functionalities. In order to incorporate P groups on carbon surfaces, various carbon nanofibers (CNFs) with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 51 publications
1
21
1
Order By: Relevance
“…XPS analysis confirmed the presence of P on the catalyst surface. Single P peaks with BE in the range of 133.5-134.0 eV revealed that P is prevalently present as phosphate groups in all the catalysts, as reported in our previous work [45]. Compared with the reference XPS data from bulk metal materials (84.0 eV and 71.0 eV for Au 4f 7/2 and Pt 4f 7/2 , respectively), slight shifts toward higher binding energy were observed in both Au and Pt XPS peaks.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…XPS analysis confirmed the presence of P on the catalyst surface. Single P peaks with BE in the range of 133.5-134.0 eV revealed that P is prevalently present as phosphate groups in all the catalysts, as reported in our previous work [45]. Compared with the reference XPS data from bulk metal materials (84.0 eV and 71.0 eV for Au 4f 7/2 and Pt 4f 7/2 , respectively), slight shifts toward higher binding energy were observed in both Au and Pt XPS peaks.…”
Section: Resultssupporting
confidence: 85%
“…A portion of these materials have been functionalized, introducing phosphorus-containing groups on the surface. We have previously shown that the surface chemistry of CNFs, in particular the graphitization degree, could influence the amount of introduced P [45]. XPS analysis has shown the presence of 1.19% of P on the surface of P-HHT-CNFs, whereas a lower amount has been observed for P-PS-CNFs and P-LHT-CNFs (0.23% and 0.24%, respectively, Table 2).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The lowest BE species (i. e. O a ) was assigned to double bonded oxygen to carbon in carbonyls and quinones as well as non‐bridging oxygen in the phosphate group (P=O). O b species could be assigned to C−O−C ether groups, esters, phenolic groups (C‐OH), anhydrides and lactones as well as C−O−P species . The highest BE peak (i. e. O c ) was assigned to C−O, non‐carbonyl oxygen in esters and anhydrides, carboxyl groups, adsorbed water and P−O‐P pyrophosphate groups ,.…”
Section: Resultsmentioning
confidence: 97%